LOKALITAS TARJAMAH HADITS BAHASA BETAWI: Respon Guru Mughni Terhadap Nilai Religius dalam Kitab Taudhih al Dalail fi Tarjamah Hadits al Syamail - Syarifah, Umaiyatus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2012)
Taudhih al-Dalail fi Tarjamah Hadits al-Syamail is the manuscript hadith of Betawi’s clerical work. The book is a translation of Muhammadiyah Syamail written by al-Tirmidhi which teaches about the person and the attitude of the Prophet both in worship and social. It is translated by Guru Mughni of Kuningan, using the Arabic alphabet in Betawi Malay in 1926 AD. Guru Mughni categorized on the most popular one of the clergy late 19th and early 20th century in Batavia. With his compatriot friend, he was able to widen the intellectual influences that reach almost all parts of Batavia at the time. Social conditions of the religious community in Betawi during the Dutch colonial inspire Guru Mughni to build strong personal and character of Betawi community by making the Holy Prophet as a role model in life. Family background and education also makes his work has its own uniqueness over the works of Indonesian scholars at that time.